Case report: Long-term efficacy and safety of semaglutide in the treatment of syndromic obesity in Prader Willi syndrome - case series and literature review - Koceva, Andrijana; Mlekuš Kozamernik, Katarina; Janež, Andrej; Herman, Rok; Ferjan, Simona; Jensterle, Mojca (Frontiers in Endocrinology, 2025)
IntroductionPrader-Willi syndrome (PWS) is the most prevalent cause of syndromic obesity. Obesity development in PWS is driven by dysfunction in neural pathways involved in satiety and reward, dysregulation in hormones regulating satiety and food intake, altered body composition and reduced energy expenditure, as well as the presence of various hormone deficiencies. As hyperphagia, satiety dysfunction and consequent food-seeking behaviors are intrinsic to PWS, obesity management can be challenging.Case seriesWe present a long-term follow-up of treatment with GLP-1 receptor agonist (GLP-1 RA) semaglutide in three patients with PWS without diabetes, one of whom had previously undergone metabolic surgery. Semaglutide treatment at dosages from 0.5 mg to 2 mg weekly demonstrated variable efficacy, from preventing further weight gain in patient 1, to achieving weight loss of up to 14.4% and 11% relative to baseline, in Patient 2 and Patient 3. It was well tolerated, even after metabolic surgery.ConclusionLong-term randomized placebo-controlled trials with larger sample sizes are needed to provide stronger evidence on the long-term efficacy and safety of semaglutide for obesity treatment in PWS as well as explore the potential synergistic effects of GLP-1 RA treatment combined with other therapeutic interventions.